1987
DOI: 10.1056/nejm198702123160704
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proximal Duodenal Mucosal Bicarbonate Secretion in Patients with Duodenal Ulcer

Abstract: The defensive factors that prevent the human duodenal mucosa from acidic and peptic damage have not been fully evaluated. To determine whether duodenal mucosal bicarbonate production was altered in patients with inactive duodenal ulcer, we measured basal and acid-stimulated bicarbonate output from the duodenal bulb and the distal duodenum in healthy subjects and patients with inactive duodenal ulcer. As compared with 16 normal subjects, the 12 patients had significantly less mean (+/- SE) basal proximal duoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(88 citation statements)
references
References 19 publications
1
86
0
1
Order By: Relevance
“…A number of studies demonstrated a close relationship between the mucosal ulcerogenic response and the duodenal HCO 3 -disorder [12,13,29] . Indeed, it is reported that patients with inactive duodenal ulcers have decreased production of HCO 3 -in the proximal duodenum during exposure to acid [30] , though the exact mechanism involved remains unknown. In the present study, perfusion of the proximal duodenum with 100mM HCl for 4h produced extensive hemorrhagic damage in rats in the presence of indomethacin.…”
Section: Figurementioning
confidence: 99%
“…A number of studies demonstrated a close relationship between the mucosal ulcerogenic response and the duodenal HCO 3 -disorder [12,13,29] . Indeed, it is reported that patients with inactive duodenal ulcers have decreased production of HCO 3 -in the proximal duodenum during exposure to acid [30] , though the exact mechanism involved remains unknown. In the present study, perfusion of the proximal duodenum with 100mM HCl for 4h produced extensive hemorrhagic damage in rats in the presence of indomethacin.…”
Section: Figurementioning
confidence: 99%
“…Regulated HCO 3 Ϫ secretion is also required for mucosal defense against luminal acid (via neutralization) in the upper gastrointestinal (GI) tract and bacteria (via stimulation of mucus secretion and maintenance of intestinal barrier function) in the lower GI tract, the defect of which has been shown to be a risk factor for peptic ulcer diseases (2,20,28) and intestinal inflammation (24,51,52). The role of CaSR in basal and acid-induced HCO 3 Ϫ secretion is unknown although a recent study with gut-specific CaSR knockout mice suggests that this receptor is crucial for mucosal defense and immunity (15).…”
mentioning
confidence: 99%
“…Duodenal mucosal bicarbonate secretion (DMBS) is considered the main mechanism in duodenal protection against acid discharged from the stomach, and this secretion is impaired in patients with acute and chronic duodenal ulcer disease (14). Acid in the duodenal lumen is the main physiological stimulus of bicarbonate secretion, and the HCl-induced rise in secretion is in part mediated by endogenous prostaglandins and neural reflexes (25).…”
mentioning
confidence: 99%